TEOLOGI AL MA’UN: ANALISIS KONTRIBUSI PEMIKIRAN EKONOMI ISLAM DALAM PENYEBARAN KEBAIKAN - Idrus, Ali; Haezah Fahriah, Putri; Gunawan, Agus; Fatma Kartika, Rini (MISYKAT AL-ANWAR JURNAL KAJIAN ISLAM DAN MASYARAKAT, 2025)
This study aims to examine the contribution of Islamic economic thought in spreading goodness by referring to Surah Al-Ma'un in the Quran. This research uses a qualitative approach with library research methods. The results show that the principles of Islamic economics contained in Surah Al-Ma'un can be implemented in the modern economic context to enhance social welfare and fair wealth distribution. Surah Al-Ma'un also emphasizes the importance of good deeds of a social nature in daily life. Keyword: Islamic economics, Surah Al-Ma'un, kindness, social welfare, wealth distribution.